The diversity of fisheries based livelihoods in the Berau Delta, East Kalimantan - Gunawan, Bambang Indratno (Wacana, Journal of the Humanities of Indonesia, 2016)
Fisheries based livelihoods in the Berau Delta are diverse. The everyday life of small-scale fishers shows that gear diversification, changing fishing gear over a lifetime and practical knowledge to access good fishing grounds in the rich coastal waters are the main livelihood strategies developed by fishers. Fishing practices in the coastal frontier of Berau are influenced by the Bugis habitus of patronage networks between the punggawa and the dependent fishers. An essential element in the decision making of fishers is their embeddedness in political-economic patronage networks as the result of values, interests and knowledge contestations. Livelihood trajectories of different fishers from various classes confirm that as social actors, whether rich or poor, they have the agency to search for better livelihoods.